Electron density and bonding in crystals : principles, theory and x-ray diffraction experiments in solid state physics and chemistry /: principles, theory and x-ray diffraction experiments in solid state physics and chemistry. (2020) - Tsirelson, V. G (Vladimir G.); Ozerov, R. P (Ruslan Pavlovich), 1926-
No abstract available